Democratization through migration? political remittances and participation of Philippine return migrants - Kessler, Christl; Rother, Stefan (Lexington Books, 2016)
This book spearheads a new area of research-the link between migration and democratization. It argues that return migrants can play an important role in the consolidation process of young democracies.